Pengaruh Model Pembelajaran CTL (Contextual Teaching and Learning) terhadap Kemampuan Kolaborasi dan Hasil Belajar Siswa SMA pada Pembelajaran Biologi - Syafitri, Nur Anita; Jailani; Nasution, Ruqoyyah; Makkadafi, Suparno Putera; Masitah (UNIB Press, 2025)
Grade X students of SMA Negeri 2 Bontang experienced problems of low biology learning outcomes and lack of collaboration skills due to conventional teacher-centered learning. This study aimed to determine the effect of implementing the CTL (Contextual Teaching and Learning) model on students' collaboration skills and learning outcomes. The CTL model emphasizes active student involvement in the learning process, connecting material with real-life contexts, and encouraging collaboration and group discussion. This study used a quantitative approach with a quasi-experimental method and a non-equivalent control group design. Sampling was carried out by purposive sampling, with class X5 as the experimental class implementing the CTL model and class X6 as the control class using conventional methods. Data analysis was carried out using the N-Gain test and the Independent Sample t Test. The results showed that the experimental class had an N-Gain value of 0.72 (high category) while the control class had 0.59 (moderate category). The t test showed a significance value of 0.000 <0.05 for collaboration skills and learning outcomes. These results indicate a significant difference between the experimental class and the control class after the CTL model was implemented. Based on these results, it can be concluded that the application of the CTL model has a positive and significant effect on improving the collaboration skills and learning outcomes of class X students of SMA Negeri 2 Bontang in biology subjects.